Implementation and Evaluation of Purchase Module Using Odoo at The Directorate of Facilities and Infrastucture of Al-Azhar Indonesia University - Khoirunisa, Amanda; Hidayat, Syarif; Arifin, Miftah; Aribowo, Budi (EXSACT-A, 2024)
Enterprise Resource Planning (ERP) is an integrated management information system that can provide specific information system requirements for each department in a company. However, its implementation requires high costs, so some companies switch to using Open ERP. Seeing this, Al-Azhar Indonesia University began to integrate its data by creating an ERP system called Application World Wide (AWW) at the Directorate of Facilities and Infrastructure. However, based on the results of interviews with the staff, it was stated that, in the management process, all Purchase Order (PO) data recorded in the system could not be downloaded, so the staff recorded data manually. To overcome this, it is necessary to develop an ERP system to support the procurement process, so that the process of recording and storing documents can be well integrated. In this study, the authors used the ERP system implementation, namely Rapid Application Development (RAD) and used the Odoo software version 16.0. A User Acceptance Test (UAT) is also carried out to find out whether the system meets the user's needs or not. After implementing Odoo at the Directorate of Facilities and Infrastructure at Al-Azhar University Indonesia, it can be concluded that all procurement activities can be recorded in a complete, correct, up-to-date, and valid/legal manner due to the implementation of the Odoo ERP system which is integrated and adapted to user needs, such as customize 4 of 12 features in the purchase module. Then with the purchase report module it can simplify the process of recording, and reporting PO data. Based on the UAT results, it can be seen that the whole question have an average score of 4.22 so it can be said that the user understands how to operate the Odoo ERP system and the features in Odoo can meet user needs.Keywords – Enterprise Resource Planning (ERP), Odoo, Rapid Application Development (RAD), User Acceptance Test (UAT)